Literasi Membangun Jiwa Kewirausahaan, Kreatif dan Inovatif di Kecamatan Tualang Kabupaten Siak - Virna Museliza; Rimet Rimet; Nanda Suryadi (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2023)
Entrepreneurs are most drivers of change, innovation, and progress in a country. An entrepreneur is someone who creates a business that faces risks and uncertainties to make a profit and experience growth by identifying opportunities and utilizing the necessary resources. Today there are many entrepreneurship opportunities for everyone keen to see these business opportunities. An entrepreneurial career can support the welfare of society and provide many choices of goods and services for domestic and foreign costumers. The participants in this community service are the ladies and gentlemen of the tourism awareness group or Pokdarwis and the community in the Tualang District of Siak Regency who want a change in managing the Tourism Village, where Perawang Barat Village has its uniqueness and attractiveness, namely the Jelutung Sikai Forest with the size of jumbo wood, along with the monkeys and birds that inhabit it and have areas that are still thick with rural nature and traditionality, have unique regional contours that are very suitable for developing camp activities, so it is very suitable to be developed as a Tourism Village. Community service with the theme of Literacy builds an entrepreneurial, creative, and innovative spirit in Tualang District, Siak Regency. The aim is to inform the community about the importance of building an entrepreneurial, creative, and innovative spirit in Tualang District, Siak Regency. And to provide information to the community about the importance of becoming a successful, creative, and innovative entrepreneur in Tualang District, Siak Regency.